Identify the Category of Arabicized Noun in Arabic Words - Ma'nawi, Arief; Megawer Sakran, Megawer Sayyid (Diwan : Jurnal Bahasa dan Sastra Arab, 2024)
تحتوي اللغة العربية على أسماء تتشكل عادةً في عملية الاشتقاق. هذا التشكيل هو نتيجة الاشتقاق من الأفعال التي تعتمد على أنماط منتظمة. ومع ذلك، مع مرور الوقت، تلقت الأسماء العربية أسماء إضافية من اللغات الأخرى، وخاصة الإنجليزية، لتكوين أسماء جديدة. وباستخدام المنهج الوصفي النوعي حصلنا على مجموعة من الأسماء المعربة من اللغة الإنجليزية. ليس من السهل التعرف على الأسماء من اللغات الأخرى مثل الأسماء الموجودة. المقالة التالية تشرح ضرورة التعرف على شكل الاسم. من خلال تحديد خصائص الأسماء الموجودة باستخدام هذه الطريقة، يتم الحصول على الأسماء التي لها شكل يمكن التعرف عليه. الأسماء من اللغات الأخرى أو اسم المعرب يمكن أن تكون اسم الجنس ، اسم الجمع، اسم النسبة، اسم مقصور و ممدود. من حيث الشكل، يمكن أن يكون اسما واحدا و مختصرا. تشير هذه النتائج إلى الاسم المعرب الذي لا يستخدم على نطاق واسع في الجمل العربية في الوقت الحاضر. Abstract Arabic has nouns that are typically formed through the isytiqaq process. This formation results from the derivation of verbs based on regular word patterns. However, in the development of the age Arabic nouns have been enriched with additional terms from other languages, especially English to form new nouns. By using qualitative descriptive methods, we grouped Arabicized nouns derived from English. Nouns from other languages are not as easily identifiable as pre-existing Arabic nouns (ism). The following paper explains the importance of identifying the form of these nouns. By comparing the characteristics of existing nouns with this method, nouns with recognizable forms are identified. Nouns from other languages or ism mu'arrab can be classified ism jins, ism jama', ism nisbah, ism maqsur, and ism mamdud. The formation can include both single nouns and acronyms. The findings indicate that Arabicized nouns are not widely used in contemporary Arabic sentences.